Engineering skills for career success - Alexander, Charles K.; Watson, James 1935- (McGrawHill Education, 2014)
Explains the keys to success for students, helping them to learn how to acquire the skills necessary for successful through a system of examples, practice problems, and a series of end of chapter problems